2020
DOI: 10.1590/1519-6984.220519
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive metabolites in of Ginkgo biloba leaves: variations by seasonal, meteorological and soil

Abstract: Ginkgo biloba is a traditional Chinese herbal medicine containing multiple components that contribute to its notable bioactivities. Variations of seasonal, meteorological and planting soil on the phytochemicals contents in G. biloba leaves due to the effects of growth meteorological and soil parameters were investigated in this study. The leaves of G. biloba were collected from different months and place in Zhejiang province, the contents of flavones (quercetin, kaempferol and isorhamnetin) and terpene lactone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
(22 reference statements)
0
13
1
Order By: Relevance
“…It is likely that both the complex chemical structure and the biosynthetic pathway of TTLs result in a much slower response to JA-Me than to phenolic acids. The differences between the phenolic composition of G. biloba leaves in our study and previously published ones may also be due to the fact that several environmental factors modify the accumulation of secondary metabolites in plants [ 15 , 62 ].…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…It is likely that both the complex chemical structure and the biosynthetic pathway of TTLs result in a much slower response to JA-Me than to phenolic acids. The differences between the phenolic composition of G. biloba leaves in our study and previously published ones may also be due to the fact that several environmental factors modify the accumulation of secondary metabolites in plants [ 15 , 62 ].…”
Section: Discussioncontrasting
confidence: 53%
“…The application of GA significantly increased the TTL content, and the endogenous GA levels reduced in the leaves, while the IAA and ABA contents varied. In contrast, Lin et al [ 15 ] found, by studying the dynamics of changes in the contents of total TTLs and flavonoids, that October is the optimal time to harvest G. biloba leaves. An analysis of gene expression related to leaf senescence in G. biloba showed that the expression levels of most ABA- and JA-related genes increases, whereas genes related to the cytoskeleton, photosynthesis, and antioxidant biosynthesis decreases from the green leaf stage to the yellow leaf stage [ 49 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to our results, the content of three flavonol glycosides rapidly changed along with leaf developmental stages. Previous studies showed that the synthesis and accumulation of secondary metabolites in Ginkgo were a temporal variational process ( Lin et al, 2020 ; Wang et al, 2020 ; Tetali et al, 2021 ). This temporal variational process may be related to the growth differentiation balance (GDB) of plants ( Herms, 1999 ; Karasov et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of these metabolites is directly influenced by external factors such as soil conditions, temperature and water availability. Therefore, the environmental conditions in which the plant is found will determine the bioactive potential and the phytochemical profile that will be found in the extract (Lin et al, 2020).…”
Section: Phytochemical Prospectingmentioning
confidence: 99%